(untitled) (Nexo Revista Científica, 2023)
In the current work, we used a high-purity germanium (HPGe) detector to assess particular activity concentrations in Seventeen cement samples from various origins. The results have shown that the specific activity, for 226Ra, ranged from 10.6±0.7Bq/kg) in Sample No. 11 to(59.1±2.4Bq/kg)in Sample No 12, for 228Ac ranged from (6.6±1Bq/kg) in Sample No.9 to(10.5±1Bq/kg) in Sample NO.7, for 40K was ranged from (81.4±7.6Bq/kg) in Sample NO.12 to (209.5±14.1Bq/kg) in Sample No.7. The research demonstrates that the cement samples are safe to use in the construction of homes and do not offer any substantial sources of radiation hazard.